Children's Language Skills Through the Illustrated Story Method in Kindergarten - Trisasi Endah Rahayu; Hariyani Hariyani; Riska Ferlia (Universitas Negeri Makassar, 2022)
This research uses a descriptive qualitative approach; using a descriptive type of research, the problem studied in the form of an implementation method to develop language skills will be described using an exemplary system based on the results of the analysis of the issues that occur in children's language skills, especially expressive language. The data collection technique is carried out through observation; the data obtained is analyzed, and a conclusion is drawn. Activities that can be done to overcome existing problems are telling stories using pictures with listening-revealing exercises, question and answer activities, giving rewards, and telling stories using props or not. The subjects of this study were protégés in kindergartens. Based on the results of observations made by researchers, it can be concluded that children's language skills can be developed through various activities through storytelling activities using illustrated media.